2018
DOI: 10.1038/s41565-018-0117-z
|View full text |Cite
|
Sign up to set email alerts
|

2D matrix engineering for homogeneous quantum dot coupling in photovoltaic solids

Abstract: Colloidal quantum dots (CQDs) are promising photovoltaic (PV) materials because of their widely tunable absorption spectrum controlled by nanocrystal size. Their bandgap tunability allows not only the optimization of single-junction cells, but also the fabrication of multijunction cells that complement perovskites and silicon . Advances in surface passivation, combined with advances in device structures , have contributed to certified power conversion efficiencies (PCEs) that rose to 11% in 2016 . Further gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
392
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 276 publications
(407 citation statements)
references
References 35 publications
15
392
0
Order By: Relevance
“…1) and other absorber materials [710 1213 1620]. Experimental solar cell performance compared to the Shockley–Queisser SQ limit (a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and other absorber materials [710 1213 1620]. Experimental solar cell performance compared to the Shockley–Queisser SQ limit (a).…”
Section: Discussionmentioning
confidence: 99%
“…The record efficiency of 7.5% [6] is comparable to that of other less investigated materials, such as the best lead-free perovskites [7], Cu 2 O [8] and Sb 2 Se 3 [910] and outperforms bismuth-halides [1112], SnS [13] and Bi 2 S 3 [1416]. However, the efficiency of Sb 2 S 3 trails behind the more thoroughly studied material systems such as lead-based perovskites [17], organic solar cells [1819] or PbS [20], thus further technological investigation is needed. Two basic factors that impact the solar cell performance of a given material are the device architecture, which defines the mechanism of charge separation, and the deposition method for the absorber, which affects the film and electronic material quality.…”
Section: Introductionmentioning
confidence: 99%
“…[5] It has been shown that a significant improvement in QD PV performance can be achieved if the deposited PbS QD films are chemically treated to undergo ligand exchange, replacing OA with shorter ligands, such as halides and short-chain thiols, which leads to high charge conductivities within QD films, boosting the power conversion efficiency of QD PVs. [1][2][3][4] This ink can then be deposited on a substrate to form the QD PV device active layer, [1][2][3][4] with recently reported PbS QD PVs achieving 12% power conversion efficiency (PCE). In a separate synthetic step, OAcapped PbS QDs are exchanged with short ligands in solution and then suspended at a high concentration in a solvent to form an ink.…”
mentioning
confidence: 99%
“…[5] Solution-phase ligand exchange is currently the leading method of preparing the active layers in top-performing PbS QD PVs. [1] With this advancement the fabrication of the active layer is now more facile, however, the scalability of PbS QD solar cells is still uncertain. [1][2][3][4] This ink can then be deposited on a substrate to form the QD PV device active layer, [1][2][3][4] with recently reported PbS QD PVs achieving 12% power conversion efficiency (PCE).…”
mentioning
confidence: 99%
See 1 more Smart Citation